CT and PET/CT findings of primary pulmonary diffuse large B-cell lymphoma: One case report and literature review. Issue 47 (November 2017) - Bai, Yanjun; Liang, Wenjie
Abstract: Rationale: Primary pulmonary diffuse large B-cell lymphoma (PPL-DLBCL) is rare and its clinical manifestations lack specificity. In this report, we present one case of PPL-DLBCL with complete clinical and imaging data, including uncontrast-enhanced CT, contrast-enhanced CT, and positron emission tomography (PET)/CT. Previous cases will also be reviewed and summarized. Patient concerns: A 62-year-old woman was hospitalized due to a swelling pain located in the right side of her back that persisted for >1 month. Local CT examination indicated a pulmonary infection and anti-infective therapy was administered; however, her symptoms did not improve. In the hospital, a lung CT scan with enhancement showed hyperintensity of the right upper lobe (RUL), ill-defined margins, inhomogeneous density, with air bronchograms, and mild-to-moderate enhancement. PET/CT showed a slight hyperintensity of mass with high uptake (about 14.7 standardized uptake value [SUV]), and no high uptake was found in other locations. Interventions: A CT-guided percutaneous needle biopsy with Tru-Cut needles was performed. Diagnoses: The final diagnosis was PPL-DLBCL. Outcomes: After 4 rounds of chemotherapy using the rituximab-cyclophosphamide hydroxydaunorubicin oncovin prednisolone (R-CHOP) regimen, the patient's pain was significantly relieved. Lessons: Finally, the PPL-DLBCL manifestation was similar to other types of PPL clinical manifestations and CT manifestations, but the PPL-DLBCL PET/CT showed an apparent, high metabolism. CT-guided percutaneous transthoracic needle biopsy can clearly diagnose the disease.